ON DIFFERENT TREATMENTS FOR DIFFERENT TYPES OF SYSTEM COMPLEXITY - Tarasenko, F.P. (IJRDO -Journal of Computer Science Engineering, 2017)
A systems view of the world is currently the dominant paradigm in modern human practice. And in all practical cases the main concern is to overcome difficulties that stem from complexity of a system under consideration. But the “complexities” have various origins of a different nature and thus require different approaches to tackling each of them. The paper discusses these differences.